Enzymatic Reactions and Phylogenetic Analysis of Haloversatile Bacteria Isolated from camalti Saltern Salt Samples used in the Leather Industry - (:unkn) unknown (AMER LEATHER CHEMISTS ASSOC, 2019)
Camalti Saltern is one of the large seawater-based saltern located in Izmir, Turkey. The crude solar salt from Camalti Saltern is used in leather industry. This type of salt may harbor viable microbial population which can spoil leather products during the curing process for hide/skins. Therefore, the objectives of this research were to isolate haloversatile bacteria from salt samples collected from Camalti Saltern, to identify these isolates using both conventional and molecular methods, and to determine their hydrolytic enzymes such as protease, lecithinase, cellulase, lipase, deoxyribonuclease, pullulanase, amylase, urease, caseinase, xylanase and esterase. In addition, damage caused by lipase and protease producing haloversatile bacteria to the structure of salted sheep skins was examined. The effects of different salt concentrations, pH and temperature values on the growth of haloversatile isolates were also investigated. Sixty-nine isolates of aerobic Bacteria showing different colony morphology, pigmentation, colony shape, and size were selected for characterization of the isolates. Phylogenetic analysis showed isolates belonging to the genera Staphylococcus (9 species), Exiguobacterium (3 species), Bacillus (11 species), Microbacterium (3 species), Gordonia (1 species), Kocuria (3 species), Paracoccus (2 species), Micrococcus (2 species), Acinetobacter (1 species), Brevibacterium (1 species), Pseudomonas (1 species), Agrococcus (1 species), Sanguibacter (1 species) and Virgibacillus (1 species). The haloversatile isolates were able to produce different enzymes such as catalase (100%), oxidase (80%), protease (52%), lecithinase (51%), cellulase (33%), lipase (23%), deoxyribonuclease (17%), pullulanase (10%), amylase (7%), urease (4%) and caseinase (4%). Scanning electron micrographs of sheep skins showed that catabolic activities of haloversatile bacterial species found in crude salt were responsible for decomposition of skins. When the crude salt containing haloversatile bacteria is used as a preservative for skins, these haloversatile bacteria may damage skin structure.
Keywords: MODERATELY HALOPHILIC BACTERIA; SP NOV.; MOLECULAR-IDENTIFICATION; SHEEP SKINS; ARCHAEA; POPULATIONS; DIVERSITY; QUALITY; SALINE; LAKE